A STUDY ON BLOOD PARAMETERS OF BARBUS XANTHOPTERUS , BARBUS SHARPEYI AND THEIR HYBRID - Abed Al. Majeed H. Talal; Jassim H. Saleh. Amer A. .Jabir (Basrah Journal of Veterinary Research)
The blood parameters of Red Blood Cells for Barbus xanthopterus, Barbus sharpeyi and B. xanthopterus X B sharpeyi (hybrid )were mentionted. The dimentions of Red Blood Cells ( length and width) for the fish B.xanthopterus, B.sharpeyi and their hybrid were as follows: (6 and 4 microns; 5 and 3 microns; 6 and 4 microns). Hb content values for the above mentioned fish, were as follows: 5.18, 5.323 and 4 g /100 ml. PCV values for the above mentioned fish were as follows: 68.25% , 100% and 42.85714%. RBC numbers for the above fish were also mentioned as follows: 3450000, 3550000 and 3300000cell/1mm3.